Lebih dari sekedar hiburan: Menelisik peran musik dalam kehidupan akademik dan sosial mahasiswa - Arifin, Hilda Fauzia (Maliki Interdisciplinary Journal, 2025)
This research is conducted based on the observation of the high frequency of music involvement in daily activities and work. Specifically for the student population, music has become an essential element and easily accessible form of entertainment, playing its own distinct role both emotionally and socially. The focus of this study is to identify and synthesise findings from various scientific literature regarding the specific impact of music on students. The method employed is the Literature Review (Studi Pustaka). The results of the literature review indicate a significant influence of music on students' academic and personal lives. Consciously or unconsciously, music is found to have many positive impacts and affects students comprehensively. These impacts include the enhancement of emotional regulation, functioning as a mood booster supporting daily activities, and potentially serving to improve mental health for its listeners. This conclusion is reinforced by the consistency of research findings that have discussed the positive effects of music on the quality of life and effectiveness of students' daily activities.